Non-invasive wearable electrochemical sensors for continuous glucose monitoring - Sameera Sh. Mohammed Ameen; Khalid M. Omer; Fotouh R. Mansour; Alaa Bedair; Mahmoud Hamed (Electrochemistry Communications)
Diabetes is an increasingly prevalent chronic condition affecting millions worldwide. Regularly monitoring blood sugar levels is essential for managing the disease effectively. The growing importance of wearable sensors across diverse sectors lies in their ability to non-invasively monitor health parameters, support disease management, improve safety, and offer valuable research insights. Non-invasive blood glucose monitoring has become a global focus of research, offering hope for many patients. Continuous glucose monitoring surpasses the limitations of traditional finger-stick tests, enabling timely interventions for better management. This review article examines recent progress and obstacles in developing non-invasive epidermal electrochemical glucose sensors. It explores methods utilizing biological fluids such as skin interstitial fluid, sweat, tears, and saliva, highlighting both advantages and limitations in device advancements. Furthermore, the review outlines future directions in glucose detection technology and its potential to enhance patients' quality of life.